Estimation of anthropogenic noise effect on relative gravimeters using the COVID-19 pandemic period - PÉNZEŠOVÁ, Laura; JANÁK, Juraj (Contributions to Geophysics and Geodesy, 2024)
The COVID-19 pandemic caused by the SARS-CoV-2 virus has brought many, mostly negative, effects and consequences on human lives, health, and economic issues. However, one of the very few positive side effects of lockdown measures was a less noisy and less loaded natural environment on a global scale. Many accurate geophysical instruments are negatively affected by the noise forced by all kinds of human activities, such as traffic, mining, construction, and others. In this paper, we present our attempt to estimate the influence of anthropogenic noise in the seismic band on five superconducting gravimeters and one spring gravimeter incorporated in International Geodynamics and Earth Tide Service (IGETS) using a comparison of gravity records before and during the lockdown period. For quantification of a noise, the mean power spectral density (PSD) was used. Based on this experiment we can compare and quantify how much particular IGETS stations and instruments are affected by the anthropogenic noise. For our experiment, we used Level 1 IGETS data on selected stations with a 1-second sampling rate or 1-minute time resolution where 1-second was not available. For selected stations we estimated the contribution of anthropogenic noise to the total noise in a seismic frequency band for a particular station and instrument.